Changes for Kirsten : a winter story - Shaw, Janet Beeler, 1937-; Graef, Renee (Madison, Wis. : Pleasant Co., 1988)
A tough Minnesota winter brings many changes to Kirsten's frontier life, including the new responsibility of helping her brother Lars set his traps and a move into a new house for her family.
"1854"--Cover.
"Book six"--Cover.
"Ages 7 and up"--P. [4] of cover.
650
Accelerated Reader AR
Keywords: Family life -- Fiction; Frontier and pioneer life -- Fiction; Minnesota -- Fiction